Isolation, Identification, and Characterization of Polystyrene-Degrading Bacteria From the Gut of Galleria Mellonella (Lepidoptera: Pyralidae) Larvae - Jiang, Shan; Su, Tingting; Zhao, Jingjing; Wang, Zhanyong (Frontiers in Bioengineering and Biotechnology, 2021)
Polystyrene (PS) is a widely used petroleum-based plastic, that pollutes the environment because it is difficult to degrade. In this study, a PS degrading bacterium identified as Massilia sp. FS1903 was successfully isolated from the gut of Galleria mellonella (Lepidoptera: Pyralidae) larvae that were fed with PS foam. Scanning electron microscopy and X-ray energy dispersive spectrometry showed that the structure and morphology of the PS film was destroyed by FS1903, and that more oxygen appeared on the degraded PS film. A water contact angle assay verified the chemical change of the PS film from initially hydrophobic to hydrophilic after degradation. X-ray photoelectron spectroscopy further demonstrated that more oxygen-containing functional groups were generated during PS degradation. After 30 days of bacterial stain incubation with 0.15 g PS, 80 mL MSM, 30°C and PS of Mn 64400 and Mw 144400 Da, the weight of the PS film significantly decreased, with 12.97%±1.05% weight loss. This amount of degradation exceeds or is comparable to that previously reported for other species of bacteria reported to degrade PS. These results show that Massilia sp. FS1903 can potentially be used to degrade PS waste.